2014
DOI: 10.1007/s10072-014-1685-9
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of 18β-glycyrrhetinic acid following oxidative and neuronal damage in brain tissue caused by global cerebral ischemia/reperfusion in a C57BL/J6 mouse model

Abstract: This study investigated the effects of 18β-glycyrrhetinic acid (GA) on neuronal damage in brain tissue caused by global cerebral ischemia/reperfusion (I/R) in C57BL/J6 mice. All subjects (n = 40) were equally divided into four groups: (1) sham-operated (SH), (2) I/R, (3) GA, and (4) GA+I/R. The SH group was used as a control. In the I/R group, the bilateral carotid arteries were clipped for 15 min, and the mice were treated with the vehicle for 10 days. In the GA group, mice were given GA (100 mg/kg) for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…It also significantly reduced the generation of excessive NO, PGE2 and ROS, inhibited the protein and mRNA levels of iNOS and COX-2 and suppressed the release of LPS-induced TNF-a, IL-6 and IL-1b in a dose-dependent manner (Wang et al 2011;Ishida et al 2013). It has been studied in indomethacin-induced small intestinal damage (Ishida et al 2013), LPS-induced macrophages (Wang et al 2011) in vitro and neuronal damage caused by global cerebral ischaemia/reperfusion in C57BL/J6 mouse models (Oztanir et al 2014) in vivo, and the anti-inflammatory actions were significantly affirmed.…”
Section: B-glycyrrhetinic Acidmentioning
confidence: 99%
“…It also significantly reduced the generation of excessive NO, PGE2 and ROS, inhibited the protein and mRNA levels of iNOS and COX-2 and suppressed the release of LPS-induced TNF-a, IL-6 and IL-1b in a dose-dependent manner (Wang et al 2011;Ishida et al 2013). It has been studied in indomethacin-induced small intestinal damage (Ishida et al 2013), LPS-induced macrophages (Wang et al 2011) in vitro and neuronal damage caused by global cerebral ischaemia/reperfusion in C57BL/J6 mouse models (Oztanir et al 2014) in vivo, and the anti-inflammatory actions were significantly affirmed.…”
Section: B-glycyrrhetinic Acidmentioning
confidence: 99%
“…The mechanisms of the anti-inflammatory activity of licorice have been explored deeply. It has been widely accepted that GC and 18β-GA suppress proinflammatory cytokine COX-2, iNOS, TNF-α, HMGP 1, PGE2, myeloperoxidase, DPPH radicals, IL-6, IL-10, TGF-β, and NF-κB, inhibit the translocation of toll-like receptor 4 to lipid rafts, and activate ABCA1 [31][32][33][34][35][36][37][38]. GLD and ISL inhibit the release of NO and IL-1β [39], and LID and LIA inhibit the activation of NF-κB p65 and the secretion of IL-6, chemokine (C-C motif) ligand 5, MMP-7, MMP-8, and MMP-9 [40].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…In vivo and clinical studies have shown that GC has been used in the postischemic brain with a middle cerebral artery occlusion mouse model [31], in an LPS-induced acute lung injury mouse model, and in a mastitis mouse model [33,34]. GA has been used to treat oxidative and neuronal damage in brain tissue caused by global cerebral ischemia/reperfusion in a C57BL/J6 mouse model [38]. LCA has been used in childhood atopic dermatitis and in a murine model of asthma [44,45].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Oxidative stress, which plays a vital role in the pathogenesis of cerebral I/R injury [5, 6], is caused by an imbalance between the production of ROS and its effective removal by endogenous scavenger enzymes and protective antioxidants [7]. Oxidative modification of intracellular molecules, such as proteins, lipids, and DNA, by ROS leads to neuronal injury and necrosis [8, 9]. …”
Section: Introductionmentioning
confidence: 99%